IMF Staff papers : Volume 39 No. 4. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1992)
Common issues emerging from the recent experience with IMF-supported programs in Hungary, Poland, Czechoslovakia, Bulgaria, and Romania are analyzed. These comprise the initial price overshooting and output collapse and the financial and structural problems associated with bad loan portfolios and sluggish implementation of privatization programs. Substantial success has been achieved in the initial microstabilization and opening-up effort. But difficulties with fiscal and monetary control may be emerging as a result of social and political pressures and unclear policy signals on the micro issues involving the structural transformation of the productive and financial systems.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet